Identification of flavouring substances of genotoxic concern present in e-cigarette refills. (January 2021) - Barhdadi, Sophia; Mertens, Birgit; Van Bossuyt, Melissa; Van De Maele, Jolien; Anthonissen, Roel; Canfyn, Michael; Courselle, Patricia; Rogiers, Vera; Deconinck, Eric; Vanhaecke, Tamara
Abstract: E-cigarettes have become very popular, a trend that has been stimulated by the wide variety of available e-liquid flavours. Considering the large number of e-liquid flavours (>7000), there is an urgent need to establish a screening strategy to prioritize the flavouring substances of highest concern for human health. In the present study, a prioritization strategy combining analytical screening, in silico tools and literature data was developed to identify potentially genotoxic e-liquid flavourings. Based on the analysis of 129 e-liquids collected on the Belgian market, 60 flavourings with positive in silico predictions for genotoxicity were identified. By using literature data, genotoxicity was excluded for 33 of them whereas for 5, i.e. estragole, safrole, 2-furylmethylketon, 2, 5-dimethyl-4-hydroxyl-3(2H)-furanone and transhexanal, there was a clear concern for in vivo genotoxicity. A selection of 4 out of the remaining 22 flavourings was tested in two in vitro genotoxicity assays. Three out of the four tested flavourings induced gene mutations and chromosome damage in vitro, whereas equivocal results were obtained for the fourth compound. Thus, although there is a legislative framework which excludes the use of CMR compounds in e-liquids, flavourings of genotoxic concern are present and might pose a health risk for e-cigarette users. Graphical abstract: Image 1 Highlights: Although not legally permitted, flavourings of genotoxic concern are present in e-liquids. A prioritization strategy was developed to identify potentially genotoxic flavourings. The prioritization strategy includes a combination of chemical analytical screening, in silico and in vitro testing.